The Analysis of Acute Heart Failure Severity and Therapeutic Response in the Emergency Department: Analysis of Acute Heart Failure Severity and Therapeutic Response in the Emergency Department - Ajartha, Ronny (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Acute heart failure (AHF) is a serious medical condition that requires immediate treatment in the emergency department (ED). This study aims to analyze the severity of AHF and the response to therapy given in the ED. This retrospective study involved 150 patients diagnosed with AHF in the ED of Lubuk Pakam General Hospital during the period of January 2023 to December 2024. Demographic data, clinical outcomes, and response to therapy were taken from patient medical records. The results showed that 60% of patients had high severity AHF, while the other 40% of patients had moderate severity. The most common initial therapies given were diuretics (80%), vasodilators (60%), and inotropics (40%). Analysis of the response to therapy showed that 70% of patients showed significant clinical improvement within the first 48 hours. Factors that influenced the response to therapy included age, comorbidities, and delay in treatment. This study concluded that the severity of AHF and response to therapy varied widely in the ED, and rapid and appropriate intervention is essential to improve patient clinical outcomes.